PENGARUH KONSELING GIZI DENGAN MEDIA BUKU SAKU TERHADAP PERILAKU MAKAN PASIEN HNP (HERNIA NUCLEUS PURPOSUS) DI KLINIK SYARAF DR. KOLMAN SARAGIH MEDAN - Zahara, Ratna; Angkat, Abdul Hairuddin (Poltekkes Kemenkes Medan, 2020)
ABSTRACT   Hernia Nucleus Pulposus (HNP) is a disease, where soft pads between vertebrae are compressed and broken, resulting in narrowing, being overweight will increase the burden on the spine and pressure on the disc, so maintaining weight with balanced nutrition will be very helpful sufferers in an effort to maintain and improve the state of HNP. This research was conducted to determine the effect of nutritional counseling with pocket media on the eating behavior of HNP (Hernia Nucleus Pulposus) patients in the Neurology Clinic dr. Kolman Medan. This type of research is a quasi-experimental (Quasy experiment) with a non-randomized one group design pre-test post-test design, without a control group. Held in July - August 2019, the sample was an outpatient who was diagnosed with HNP (Hernia Nucleus Purposus) who was treated at the Neurology Clinic dr. Kolman, who was selected by